Effective General and Homoeopathic Cardiac Care for Elderly People in CHD (Heart Attack) (Homoeopathy for All, 2023)
Cardiovascular disease is the  most frequent diagnosis in elderly  people and it is the leading cause  of death in both men and women  older than 65 years of age. The  high morbidity and mortality from  cardiovascular disease warrant  aggressive approaches to prevention  and treatment that have been shown  to be effective in older patients.  This article provides an overview  of the aetiology, diagnosis, and  appropriate general & homoeopathic  management of coronary heart  disease (heart attack) for elder  peoples.
Keywords: homoeopathic; cardiovascular; diagnosis